FIRST-ORDER ULTRAVIOLET DERIVATIVE SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF RESERPINE IN ANTIHYPERTENSION TABLET - Latifah K Darusman; Mohamad Rafi; Wulan Tri Wahyuni; Rizna Azrianiningsari (Universitas Gadjah Mada, 2012)
A new ultraviolet derivative spectrophotometry (UVDS) method has been developed for determination of reserpine in antihypertension tablets. A first-order UVDS based on the measurement of the distance between peaks to baseline (DZ) at the wavelength of 312 nm was used. Evaluation of analytical performance showed that accuracy as percentage recovery was 99.18-101.13%, precision expressed as relative standard deviation (RSD) was 1.91% and linear correlation was also obtained 0.9998 in the range of 10-50 µg/mL. Estimation of limit of detection and limit of quantitation was 0.8868 µg/mL and 2.6874 µg/mL, respectively. As a reference method, HPLC methods from United States Pharmacopiea (USP) were used. Commercially tablets available were analyzed by the two methods. The content of reserpine in tablets was found 0.2260±0.0033 mg by UVDS and 0.2301±0.0051 mg by the USP methods. The result obtained from the two methods was compared statistically using F-test and t-test and showed no significant differences between the variance and mean values of the two methods at 95% confidence level. This method was faster, easier, low cost and gave result as well as the reference method published by USP.